An efficient encryption-secure communication using symmetric key - Nigar, Nahida (International Journal of Engineering and Technology, 2019)
To stop unauthorized disclosure of confidential information we need to secure our data. To secure data we need to use a secure cryptographic system. The conventional systems of data security are not suitable for multimedia as well as different data types. This paper is concerned with the development of a secure communication system which will satisfy some aspects such as reliability, maintainability, security, and user-friendliness. This project is based on the conventional method of cryptography known as symmetric key encryption technique named AES and 3DES made the system faster, better immune to attacks, greater complexity, easier encryption/decryption, and much more advanced security feature included. This project work is designed and developed for secure communication on different platforms. Unlike any other application, this software can encrypt any length of a video message, audio, text, etc. using a key and then decrypts the ciphertext with the same key to see the plaintext on the receiving end. Whatever the data is encrypted the ciphertext will be in text type which will give more security to the data because the hacker cannot guess the data type to hack. Comparing with other security based application system, the proposed system can be used for any type of communication in both online and offline.Â Â